Partisan investment in the global economy : why the left loves foreign direct investment and FDI loves the left - Pinto, Pablo Martín (Cambridge University Press, 2013)
"Develops a partisan theory of foreign direct investment (FDI) to explain variance in the regulation of foreign investment and in the amount of FDI inflows that countries receive"--